Monetary policy and unemployment in Nigeria: Is there a dynamic relationship? - Sunday N. Essien; Garba A. Manya; Mary O. A. Arigo; Kufre J. Bassey; Suleiman F. Ogunyinka; Deborah G. Ojegwo; Francisca Ogbuehi (CBN Journal of Applied Statistics, 2016)
This paper examines the link between unemployment and monetary policy in Nigeria using a vector autoregressive (VAR) framework for the period 1983q1 - 2014q1. The paper investigates the effect of structural change by identifying three structural breakpoints and incorporating them into the VAR model as dummy variables. The results show that a positive shock to policy rate raises unemployment over a 10 quarter period. In addition, all the variables used as proxy in the model jointly Granger cause unemployment, implying the existence of a dynamic relationship between monetary policy and unemployment in Nigeria.
Keywords: E24; E51; E52; 330; Investment; Monetary Policy Rate; Money supply; Unemployment